ABC model and the management of costs - Pravdić Predrag; Kučinar Rada (Trendovi u Poslovanju)
When a company has multiple objectives at the same time, they all must be considered and balanced when making any business decisions. Linking the markets, capital and resources so as to thus ensure the highest yield is, In fact, the search for competitive advantage as a basic condition for survival in a market economy. In highly detailed systems based on the management of costs or ABC (activity based costing) systems, the cost of activities often result in erroneous evaluation of aggregate costs of the action. Improvements in information technology and monitoring decrease of technology costs enabled the ABC system to become a feasible system calculating costs in many organizations.